Curricular Integration of Interactive Graphic Organisers in Teacher Training - Lopez-Villarroel, M; Ponce-Arias, H (MINISTRY EDUCATION & SCIENCE, 2012)
Introduction: this article presents the findings of a research study on curricular integration of a software application called Interactive Graphic Organiser (IGO) in teacher training and its effect on school classroom didactic. Methodology: an action-research methodology was used with three intervention phases: first, training in the use of graphic organisers of a group of academics who were expert in didactics; second, training of a group of pedagogy students in the methodological use of graphic organisers and, third, instructional design for the IGO s integration in secondary school curricula through these students on-the-job training. Results: first, the application of a questionnaire on information and communication technology (ICT) skills shows that pedagogy students are good users of office automation applications and Internet but lack preparation for implementing meaningful learning experiences using ICT. Second, after the training process on interactive graphic organisers, each student prepared a curricular design incorporating the IGO as the teaching and learning process articulator. Third, as a result of implementing these curricular designs in schools, the pedagogy students valued this innovation in their didactic practices. Discussion: the findings demonstrate that the adequate integration of technology such as the IGO in the curriculum facilitates not only improvements in the teaching and learning process, from its design to its execution, but also constitutes an interesting didactic resource to develop basic cognitive skills, at the same time enhancing future teachers ICT skills. Conclusions: the study s results confirm that the IGO s adequate curricular integration substantially improves the didactics of the discipline in which it is incorporated.